The relationship between teachers' technology proficiencies and their levels of integrating technology into their lessons - ÇAYAK, SEMİH (My University, 2023)
This study examines the relationship between teachers' technology proficiencies and their level of integrating technology into their lessons. In this research, which was designed in a relational survey model, as data collection tools, the “Technology Proficiency SelfAssessment Scale for 21st Century Learning” developed by Christensen and Knezek and adapted to Turkish conditions by Fidan, Debbağ and Çukurbaşı (2020); and “Teachers' Technology Integration Indicators Scale” developed by Çakıroğlu, Gökoğlu and Çebi (2015) were used. The research sample consisted of 398 teachers working in public schools in Istanbul’s Pendik and Tuzla districts. The findings showed that teachers' technology proficiencies and integration levels were high. In addition, teachers' technology proficiencies and ability to integrate technology into their lessons did not show statistically significant differences according to their gender, professional seniority and education level. However, the teachers’ technology proficiency and the level of integrating technology into their lessons showed statistically significant differences according to their educational status. These differences in both variables were significantly higher for teachers with graduate education than those with undergraduate education. According to another finding from this research, there was a positive, high level and significant relationship between teachers' technology proficiency and their ability to integrate technology into their lessons. As a result of the regression analysis, it was seen that technological proficiency was a significant predictor of technology integration. Technological proficiency explains 53.9% of technology integration.
Keywords: Sosyal ve Beşeri Bilimler; Social Sciences and Humanities; Sosyal Bilimler (SOC); Social Sciences (SOC); Educational technology; Technology integration; Technology proficiency; Teacher